Peace and faith : Christian churches and the Israeli-Palestinian conflict - Nelson, Cary; Gizzi, Michael C. (Presbyterians for Middle East Peace, 2021)
"Peace and faith : Christian Churches and the Israeli-Palestinian Conflict, composed of new essays, is the first collection to bring together writers from different faith communities to discuss the Boycott, Divestment, and Sanctions movement's impact on one of the more fractious topics addressed by Christian denominations: the Israeli-Palestinian conflict. In so doing, it builds on interfaith projects under way for decades. Theology and politics intermingle in debates taking place in local churches, Christian NGOs, and national church meetings that define official policy. The debates revive and reframe the most basic values of Christianity and the questions church members seek to resolve: How do Christians today hew to the principles Jesus articulated? How can justice be pursued in the context of competing national narratives and historical understandings? What bearing do or should centuries of Christian violence against Jews and Muslims have on contemporary theology and ethics? Is it ethical, or even possible, to set aside millennia of Christian anti-Semitism in judging Israel's conduct? What Christian values should be honored in pursuing Jesus's mission of reconciliation today? How may the pursuit of truth be corrupted by passionate social witness? Can advocacy cross the line into hatred? These are among the critical questions this collection poses and attempts to address."--Publisher